Investigation of Microplastic Exposure to Marine Fish in the Marine Tourism Area of Makassar City - Marzuki, Ismail; Lestari, Selvi Ayu; Putra, Irham Pratama (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
Plastic waste pollution in the marine environment triggers the formation of microplastics dissolved in seawater. Microplastics are one of the nutrients for plankton and phytoplankton. Through the food chain, microplastics can accumulate in the bodies of marine biota, until they finally reach the human body. The purpose of this research is to investigate and determine the microplastic group in fish in Makassar City KWB destinations. The method applied is maceration extraction using 70% C2H5OH for 3 days, then extracted with N-Hexane. The non-polar extracts identified the microplastic components using FTIR spectroscopy and analyzed the types of microplastics based on their absorption spectrum images. The results of the study were that all fish samples coded PS.B.1, PS.B.2, PS.B.3, were contaminated with secondary microplastics. Types of microplastics were identified, namely PP, PVC, PE, PS, PET and PC. The microplastic contaminants are thought to be the result of community activities. The public needs to be aware of the potential for microplastic accumulation in the bodies of marine fish that are consumed. Managers of Makassar City KWB destinations are advised to apply a pattern of supervision to the community to care about waste and educate the implementation of plastic waste recycling management